A long-term oxidation barrier for copper nanowires: graphene says yes. Issue 6 (9th January 2015) - Shi, Liangjing; Wang, Ranran; Zhai, Haitao; Liu, Yangqiao; Gao, Lian; Sun, Jing
Abstract : Cu nanowire oxidation kinetics is proposed, and the protecting mechanism of transferred graphene on Cu nanowires is proved by stability investigation. Abstract : Copper nanowires (Cu NWs) hold great promise for the fabrication of low-cost transparent electrodes. However, the instability of Cu NWs has limited their application into commercial devices. Herein, CVD-grown graphene is transferred onto Cu NW films and the stability of the hybrid films over long time scale under different conditions is investigated systematically. The results reveal that the graphene–Cu NW films can maintain their efficacy ( R / R 0 < 2) after 180 days of exposure in an ambient atmosphere. Furthermore, a two-step oxidation kinetic mechanism of Cu NWs can be proposed by using Raman and X-Ray photoelectron spectroscopy. The protecting mechanism of graphene on Cu NW films is disclosed to preventing the oxygen species permeation, decelerating the oxidation from Cu to Cu2 O and hindering the oxidation of Cu2 O to CuO. These results are of referring significance to make metal nanowire based transparent electrodes with both high optical-electrical performance and excellent stability.